Digital Marketing Berbasis AI untuk Peningkatan Daya Saing UMKM Kuliner di Kabupaten Kampar - Mardiana Putri; Zulfikar Zulfikar; Doli Apriansyah (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
Culinary MSMEs are among the fastest-growing subsectors of the creative economy in Indonesia,including in Kampar Regency. However, most of them still face challenges in competitiveness,particularly in terms of limited digital literacy, marketing strategies, and technology adoption. Thisstudy aims to analyze the application of Artificial Intelligence (AI)-based digital marketing inenhancing the competitiveness of culinary MSMEs in Kampar. A mixed-methods approach wasemployed, combining quantitative surveys of 50 culinary MSMEs and qualitative in-depthinterviews with business owners. The findings reveal that AI-driven digital marketing contributesto improving promotional effectiveness, personalized content, consumer trend analysis, andproduct distribution efficiency. Nevertheless, AI adoption remains limited to basic chatbots andsales analytics, with major barriers including investment costs, low digital literacy, and limitedecosystem support. These results highlight the importance of collaboration between government,academia, and industry in strengthening the digital capacity of culinary MSMEs to compete inboth local and global markets